Antibacterial test, toxicity and food application of plant seed extracts: a review - Ahmad Sowhini, Nur Syahiba Haseena; Abdullah Sani, Muhammad Shirwan; Hashim, Yumi Zuhanis Has-Yun; Othman, Rashidi; Mahamad Maifiah, Mohd Hafidz; Mohd Desa, Mohd Nasir (2019)
Allah (Subhanahu Wa Ta'ala) has instructed mankind to eat healthy and permissible food as narrated in Al-Quran. In accordance with Maqasid as-Shari’ah, it is considered as daruriyyah to ensure the safety of food as an act of protecting life. Therefore, application of antibacterial agent on food aims to improve the consumers’ health and control the herd immunity. Plant seed is a newly emerged alternative as a source of antibacterial agents. Commonly discarded, the utilization of plant seed is not only to reduce environmental waste issue, but also as economical benefit to many industries. The aim of this article is to review the current literature on whether antibacterial test, toxicity, and application of various plant seed extracts potentially contribute to the efficacy of the seed. This review presents a comprehensive analysis of the antibacterial activity assay of the plant seed, including end point and descriptive methods, its acute, subacute and chronic toxicities, and application of the plant seed on food and textiles industries. This review was conducted using various science-based platforms, such as Science Direct, Google Scholar, Emerald etc. The keywords ‘antibacterial’, ‘antibacterial seed’, ‘seed extract’ and ‘toxicity seed’ were used in this search.